Introduction of emergency equipment for floods, fires and riots in Augmented Reality - Ichsan, Fadla; Istiono, Wirawan (International Journal of Science, Technology & Management, 2023)
Indonesia is one of the countries with a high risk of natural disasters in several regions. Emergencies can result in death or property destruction. While dealing with catastrophes, swift action and anticipation are required; yet, if the community is unfamiliar with emergency equipment, it will take longer to overcome emergencies. It turns out that many people still do not understand emergency equipment information correctly. The active engagement of the community in recognizing emergency equipment can be enhanced by the provision of information. The implementation of an application utilizing Augmented Reality technology and the Fisher Yates Shuffle algorithm aims to enhance public awareness and promote active engagement in identifying emergency equipment. Once the application has been developed and constructed, the evaluation process will involve the utilization of a pre-test, post-test, and the N-Gain Score methodology. The N-Gain Score is a valuable tool for gauging the extent of the community's comprehension in identifying emergency equipment. Additionally, a Questionnaire will be employed to evaluate the level of user satisfaction with the application. The findings of the study revealed that the level of knowledge acquired by users, as assessed, was 57%. This suggests that users demonstrate a relatively high level of proficiency in understanding emergency equipment when utilizing the application. Furthermore, the overall satisfaction of users with the program received a final score of 86%, showing a high degree of effectiveness.